Fountain, St Thomas Cathedral - Ghosh, Ayan (2023)
The fountain at St. Thomas Cathedral was donated by Parsi industrialist and philanthropist Sir Cowasji Jehangir (1812-78), from the fabulously wealthy Readymoney family, who is credited with erecting several other drinking fountains in Mumbai.